Effects of paternal obesity on maternal-neonatal outcomes and long-term prognosis in adolescents - Lin, Yingying; Chen, Zhiwei; Qian, Qinfang; Wang, Yanxia; Xiu, Xiaoyan; Ou, Ping; Fang, Jiaoning; Li, Guobo (Frontiers in Endocrinology, 2023)
Objective This study evaluated whether paternal body mass index (BMI) before pregnancy was a risk factor for maternal-neonatal outcomes and long-term prognosis in offspring. Methods This study included 29,518 participants from eight cities in Fujian, China using a stratified cluster random sampling method from May to September 2019. They were divided into four groups based on paternal BMI. Univariate and multivariate logistic regression were used to explore the relationship between paternal BMI groups, maternal-neonatal outcomes, and long-term prognosis in offspring. Further subgroup analysis was conducted to examine the stability of the risk. Results The incidences of hypertensive disorder complicating pregnancy (HDCP), cesarean delivery, gestational weight gain (GWG) over guideline, and macrosomia were significantly higher in the paternal overweight and obesity group. Importantly, this study demonstrated that the incidence of asthma, hand-foot-and-mouth disease (HFMD), anemia, dental caries, and obesity of adolescents in paternal obesity increased. Furthermore, logistic regression and subgroup analysis confirm paternal obesity is a risk factor for HDCP, cesarean delivery, and macrosomia. It caused poor long-term prognosis in adolescents, including asthma, dental caries, and HFMD. Conclusions Paternal obesity is a risk factor for adverse maternal-neonatal outcomes and poor long-term prognosis in adolescents. In addition to focusing on maternal weight, expectant fathers should pay more attention to weight management since BMI is a modifiable risk factor. Preventing paternal obesity can lead to better maternal and child outcomes. It would provide new opportunities for chronic diseases.